Leveraging on multidisciplinary expertise for landslide disaster risk reduction and management : a case study of a limestone hill rockfall hazard assessment, Batu Caves, Selangor, Malaysia - Zainab Mohamed,; Abd Ghani Rafek,; Zhang, Mingwei; Chen, Yanlong; Goh, Thian Lai; Khamarrul Azahari,; Zakaria Mohamad, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The United Nations Development Program agenda 2030 has charted out seventeen Sustainable Development Goals (SDG) whereby Malaysia as a member has strategically set the platform for growth. From the seventeen agendas, the SDG 9 (built resilient, promote inclusive and sustainable industrialization and foster innovation) and SDG 11 (make cities and human settlements inclusive, resilient, and sustainable) requires a paradigm shift from conventional engineering approach for environmentally induced disasters. Leveraging multidisciplinary ability and information and communications technology (ICT) in the landslide disaster studies had enabled regional-scale information acquirement for hazards identification, exposure, and risk assessment to meet the goals. The investigated limestone hill, Batu Caves is located within the suburban city of Kuala Lumpur. The land use around the hill is extensive and the area is highly populated with encroachment to the toe of the limestone hill. The purpose of the risk study was to assess the limestone hill’s stability and hazards and the exposure that may lead to the vulnerability of the residences and commercial activities at and around the hill. Therefore, an engineering risk assessment study was carried out to determine rock fall hazard potential. The Terrestrial Laser Scanning survey was utilized to obtain the hillside’s cross section. Discontinuity mapping was conducted to identify rock block size and rock slope was analyzed using rock mass classification system to determine rock slope quality. The rockfall analysis was conducted to identify rock rollout distance and produce rock fall hazard maps. The Slope Mass Rating for the slope BC1A, Parcel 1, Batu Caves was determined as 61, and is classified as a partially stable. The maximum rollout distance at this slope was 11 m. This illustrates the practical output of this study that can be applied for mitigation and future development of the area.